Young adults' perspectives on their psychosocial outcomes 16 years following childhood traumatic brain injury. Issue 3 (19th August 2014) - Rosema, Stefanie; Muscara, Frank; Anderson, Vicki A; Godfrey, Celia; Eren, Senem; Catroppa, Cathy; McNicholl, Declan; Wicks, Beth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Childhood traumatic brain injury (CTBI) is one of the most common causes of mortality and disability in children and adolescents that impacts on neuropsychological, social and psychological development. A disruption of development in these areas often results in long-term problems with interpersonal relationships, participation in leisure and social activities, and employment status. These social and psychological problems appear to persist longer in comparison to other functional consequences, although evidence is scarce. The aim of this study was to investigate social and psychological outcomes 15 years post injury. Design/methodology/approach Thirty-six participants post CTBI (mean age 21.47 years, SD=2.74), 16 males) and 18 healthy controls (mean age 20.94 years, SD=2.21), 12 males) were recruited from a larger sample of a longitudinal study conducted at the Royal Children's Hospital, Melbourne, Australia. Information about social and psychological functioning was collected via questionnaires completed at 15 years post-injury. Findings Results showed that post CTBI, adolescents and young adults reported elevated risk of developing psychological problems following their transition into adulthood. CTBI survivors reported greatest problems on internalizing symptoms such as depression, anxiety and withdrawal. Originality/value This is the first perspective longitudinal study investigating the young adults perspective of their long-term psychosocial outcomes following childhood traumatic brain injury.